Student health behavior and academic performance - Reuter,Peter R.; Forster,Bridget L. (PeerJ, 2021)
Objective To explore the association between health behaviors and habits of university students and academic achievement. Participants Six hundred fourteen undergraduate students at a state university in the United States. Methods Students were invited over a 2-year period to participate in an anonymous online survey that asked questions concerning a wide range of health behaviors and habits; participants were asked to report their current grade point average (GPA). Standard Least Squares Models were used to examine differences in self-reported GPA across the different health behaviors and habits, with individuals as replicates. Results The study found positive associations between breakfast consumption, physical activity, and strength training and self-reported GPA, and negative associations between the hours of sleep per night, hours worked per week, fast food and energy drinks consumption, and use of marijuana, alcohol and electronic vaping products. Conclusions While there is an association for some of the studied health behaviors and habits with self-reported GPA, the effect sizes for these health behaviors were low. The significant effect of vaping on GPA as well as the increased use reported in this study indicates that the topic should be explored further. Furthermore, students should be educated on the potential positive and negative effects of health behavior choices to help them make better choices.
Keywords: Student health behavior; College students; Grade point average; Academic performance; Healthy eating; Sleep; Working; Vaping; Breakfast; Fast food